2011
DOI: 10.1021/es201739t
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated Compounds in the Asian Atmosphere

Abstract: There is interest in the production, use, and environmental occurrence of perfluorinated compounds (PFCs) across Asia and the Asian contributions to the burden of these compounds reaching the Arctic and other remote regions via long-range transport. A spatial survey of perfluorinated compounds was therefore undertaken across China, India, and Japan in 2009 using passive air samplers. Target analytes were fluorotelomer olefins (FTOs), acrylates (FTAs), alcohols (FTOHs), sulfonamides, and sulfonamidoethanols. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
95
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 32 publications
(100 reference statements)
13
95
9
Order By: Relevance
“…This variation is consistent with the estimated atmospheric residence times of FTOHs of 80, 70, and 50 days for 8:2 FTOH, 10:2 FTOH, and 6:2 FTOH, respectively (Piekarz et al 2007). Gaseous FTOHs reported in Asia and the Pacific regions (Li et al 2011) were generally higher than those determined in the European continent and marine environment (Dreyer and Ebinghaus 2009;Jahnke et al 2007) higher than those in this study and the European atmosphere (Dreyer et al 2009a). For FASE/As, ∑FASA (3.1-26 pg m −3 , median: 7.5 pg m −3 ) and ∑FASE (3.2-19 pg m −3 , median: 6.9 pg m −3 ) were comparable in this work.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…This variation is consistent with the estimated atmospheric residence times of FTOHs of 80, 70, and 50 days for 8:2 FTOH, 10:2 FTOH, and 6:2 FTOH, respectively (Piekarz et al 2007). Gaseous FTOHs reported in Asia and the Pacific regions (Li et al 2011) were generally higher than those determined in the European continent and marine environment (Dreyer and Ebinghaus 2009;Jahnke et al 2007) higher than those in this study and the European atmosphere (Dreyer et al 2009a). For FASE/As, ∑FASA (3.1-26 pg m −3 , median: 7.5 pg m −3 ) and ∑FASE (3.2-19 pg m −3 , median: 6.9 pg m −3 ) were comparable in this work.…”
Section: Resultscontrasting
confidence: 71%
“…In this work, two fluorotelomer acrylates, 8:2 FTAC and 6:2 FTAC, were determined at relatively low levels with ranges of <0.2-4.4 and <0.9-1.2 pg m −3 , respectively. These results are two to five times lower than those reported in the North Sea and at an urban site of Hamburg (Dreyer and Ebinghaus 2009) and in the Asia-Pacific region (Li et al 2011), and 3 orders of magnitude lower than those reported in Japan (Oono et al 2008). FTACs are monomers used in the manufacturing of fluorotelomer-based polymers.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous studies reported high neutral PFAS concentrations in air along the coastal cities of the South Yellow Sea. For instance, Li et al (2011) reported neutral ∑PFAS concentrations between 113 and 306 pg/m 3 in the Yellow Sea coastal cities of China, and Kim et al (2012) reported mean concentration of ∑FTOHs and ∑FASEs + FASAs of 19,731 and 260 pg/m 3 , respectively, in the outdoor Korean air. Air masses from the Korea Peninsula coast and the Japan Sea (A9-A11) exhibited lower ∑PFAS concentrations (170 to 220 pg/m 3 ) than those from the south Yellow Sea (A1-A8, 192 to 511 pg/m 3 ).…”
Section: Distributions Sources and Gas Phase Dry Deposition Of Neutmentioning
confidence: 99%
“…Incomplete removal of PFASs by waste water treatment plants (WWTPs) (Schultz et al, 2006;Sun et al, 2011), and transport by water flow and oceanic currents (Yamashita et al, 2008) and atmosphere (Stock et al, 2007) make them ubiquitously distributed in various environmental media including air (Li et al, 2011b), water (Hansen et al, 2002;Hong et al, 2013), sediment (Higgins et al, 2005;Benskin et al, 2011), biota (Giesy and Kannan, 2001;Tao et al, 2006), and human (Hansen et al, 2001). They have even been found in some remote areas, such as the Arctic (Benskin et al, 2012) and Tibetan Plateau (Shi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%